2007
DOI: 10.1530/rep-06-0267
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide on matrix metalloproteinase 2 (MMP2) and MMP9 in placenta and fetus from diabetic rats

Abstract: Matrix metalloproteinases (MMPs) play an important role in tissue remodeling that accompanies the rapid growth, differentiation, and structural changes of the placenta and several fetal organs. In the present study, we investigated whether the diabetic maternal environment may alter the regulatory homeostasis exerted by nitric oxide (NO) on MMPs activity in the feto-placental unit from rats at midgestation. We found that NADPH-diaphorase activity, which reflects the distribution and activity of NO synthases (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Therefore, we sought to expand on the role of MMPs in pregnancy and delineate the effect of NO inhibition on the expression of MMPs in the late pregnant mUA. MMPs are key proteases involved in remodeling and have been linked to NO signaling (17,33,54). Others (32,45) have established that many MMPs and TIMPs, including MT1-MMP, MMP-2, and TIMP-2, are upregulated during rat pregnancy, especially during the day before parturition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we sought to expand on the role of MMPs in pregnancy and delineate the effect of NO inhibition on the expression of MMPs in the late pregnant mUA. MMPs are key proteases involved in remodeling and have been linked to NO signaling (17,33,54). Others (32,45) have established that many MMPs and TIMPs, including MT1-MMP, MMP-2, and TIMP-2, are upregulated during rat pregnancy, especially during the day before parturition.…”
Section: Discussionmentioning
confidence: 99%
“…Individual members of the MMP family are regulated independently (Brown et al 1990;Vincenti et al 1998). Pustovrh et al (2007) reported that MMP-9 activity was more susceptible than MMP-2 in placenta and fetus from diabetic rats which treated by nitric oxide. Both ELISA and immunohistochemistry consistently indicated that treatment with low concentrations of MCs (X group) had no obvious effect on MMP-2 expression, but could stimulate the enzyme expression in the mice exposed to the water sampled from more heavily polluted areas (M1, M2 and H group).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple linkages between cellular inputs and outputs further complicate understanding the precise mechanisms involved. For example, VEGF, estrogen, and shear stress all stimulate NO production, and both estrogen and NO regulate matrix metalloproteinase activity and, hence, passive mechanical properties and matrix composition (27, 43, 103). …”
Section: Mechanisms Underlying Gestational Uterine Vascular Remodelingmentioning
confidence: 99%